Acute Myocardial Infarction Following the Consumption of Energy Drink in a 28-Year-Old Male: A Case Report - Pedro Pallangyo MD, MPH; Smita V. Bhalia MD, MSc; Makrina Komba MPH; Zabella S. Mkojera MPH; Happiness J. Swai MD; Henry A. Mayala MD, PhD; Peter R. Kisenge MD, MSc (SAGE Publishing, 2023)
Excessive intake of energy drinks is increasingly realized to have a detrimental effect on platelet and endothelial functions with resultant hypercoagulable state and consequently increased risk of thrombosis. A 28-year-old man of African origin presented to the emergency department with an 8-hour history of retrosternal chest pain. His symptoms started 4 hours after consuming 5 cans (1250 cc) of an energy drink whose principal ingredients are caffeine, taurine, sugar, and glucuronolactone. His past medical and surgical history was unremarkable, and he had no apparent cardiovascular risk factor. Physical examination was unremarkable; however, electrocardiogram and echocardiogram showed features of anterolateral myocardial infarction (STEMI). Catheterization confirmed a 100% thrombotic occlusion of the proximal left anterior descending (LAD) artery and revascularization with a drug-eluting stent was successful. In conclusion, sudden onset of chest pain following energy drink consumption should raise an index of suspicion for acute coronary syndrome. With the preponderance of data suggesting increased incidence of energy drink-associated coronary events, it is prudent to advocate a limited consumption of such beverages.